The effect of medication and nutrition education on therapy adherence among hypertensive patients in the post-pandemic hospital setting - Saparuddin Latu (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Hypertension is a chronic condition that requires long-term adherence to pharmacological treatment and lifestyle modifications. The inadequate integration of drug education and nutrition counseling in clinical settings hinders treatment adherence, particularly after the COVID-19 pandemic. This study aimed to analyze the influence of the quality of drug education and nutrition counseling services on treatment adherence among patients with hypertension. A quantitative analytical study with a cross-sectional design was conducted at the Primaya Inco Sorowako Hospital, South Sulawesi, Indonesia, from May to June 2025. Eighty outpatients with hypertension were selected using purposive sampling based on the predefined inclusion criteria. The data were collected using validated questionnaires. Spearman’s correlation and multiple linear regression were used for analysis. The quality of drug education showed a significant positive correlation with treatment adherence (r = 0,61; p < 0,001), as did nutritional counseling (r = 0,53; p < 0,001). Both variables jointly influenced adherence (R² = 0,46), with drug education being the dominant predictor (β = 0,48; p < 0,001). These findings suggest that enhanced interdisciplinary collaboration between pharmacists and nutritionists is essential for improving adherence in patients with hypertension.